Study on the effect of sevoflurane on the cognitive function of aged rats based on the activation of cortical microglia. Issue 4 (9th December 2021) - Zhou, Jun‐Jie; Zhang, Chao; Yang, Xin‐Xin; Zhang, Xiao‐Xi; Zhang, Nai‐Xin; Fang, Xu; Zhu, Yu‐Hang; Liu, De‐Xing; Xu, Shan; Xu, Mei‐Qi; Zhu, Zhao‐Qiong
Abstract: Postoperative cognitive dysfunction (POCD) is a common clinical manifestation that is a severe complication characterized by decreased learning ability and deterioration of memory following anesthesia and surgery. However, the precise mechanisms of POCD are not completely understood. Rats were divided into blank control group (Con, n = 12) and sevoflurane group (Sev, n = 12). Morris water maze test was performed to evaluate the ability of learning and memory in two groups of rats; immunohistochemical staining was used to detect the expression of ion calcium‐binding adaptor molecule‐1 (Iba‐1) in rat prefrontal cortex (PFC); Western blot analysis was applied respectively to investigate Iba‐1, inducible nitric oxide synthase (iNOS), arginase‐1 (ARG1), inflammatory cytokines interleukin‐1β (IL‐1β), and tumor necrosis factor‐α (TNF‐α) expression; The expression of iNOS, ARG1, IL‐1β, and TNF‐α in sera of rats was detected by enzyme‐linked immunosorbent assay. We found that sevoflurane induced learning and memory impairment assessed by morris water maze test, anesthesia up‐regulated the expression of iNOS, IL‐1β and TNF‐α inflammasome in microglia, as indicated by increased activation of Iba‐1 and reduced the level of ARG1 in the PFC. We conclude that the cognitive function of rats after inhaling anesthesia was likely associated with M1/M2 polarization of microglia, which was triggered by sevoflurane. Abstract : After sevoflurane intervention, microglia in the prefrontal cortex of aging model rats were activated. M1 microglia secrete and release interleukin‐1β and tumor necrosis factor‐α to promote the occurrence of inflammatory response. However, the release of arginase‐1 by protective M2 microglia was significantly inhibited.